Coastal Downwelling Intensifies Landfalling Hurricanes. Issue 13 (6th July 2022) - Gramer, Lewis J.; Zhang, Jun A.; Alaka, Ghassan; Hazelton, Andrew; Gopalakrishnan, Sundararaman
Abstract: This study demonstrates a link between coastal downwelling and tropical cyclone (TC) intensification. We show that coastal downwelling increases air‐sea enthalpy (heat, moisture) fluxes ahead of TCs as they approach land, creating conditions conducive to intensification even in the presence of typically inhibiting factors like strong vertical wind shear. The study uses a coupled TC model (HWRF‐B) and buoy observations to demonstrate that coastal downwelling developed as three TCs in 2020 approached land. Results show downwelling maintained warmer sea‐surface temperatures over the ocean shelf, enhancing air‐sea temperature/humidity contrasts. We found that in such cases resulting air‐sea enthalpy fluxes can replenish the boundary‐layer even when cool, dry air intrudes, as in sheared storms and storms approaching continental land‐masses. The resulting warm, moist air is advected into the TC inner core, enhancing convective development, thus providing energy for TC intensification. These results indicate coastal downwelling can be important in forecasting TC intensity change before landfall. Plain Language Summary: We examined forecasts for three hurricanes in 2020 that intensified near landfall. Using a coupled air‐sea hurricane model, we found that tropical storm‐force winds blowing parallel to the coast forced water near the ocean surface to move toward shore. Winds often blow parallel to the coast when tropical cyclones (TCs) (hurricanes) are near land. The model showed that this movement of water toward shore caused water levels to rise near the coastal boundary ‐ a process called coastal Ekman convergence. This convergence forced water downward along the sloping seafloor and back away from shore, forming a circular exchange of water between the shelf and the open ocean; this exchange is called coastal downwelling. We demonstrate that incipient coastal downwelling brought warmer surface water over the shelf, heating and adding moisture to the air and thus providing more energy to these TCs. We further show that this additional energy provided by coastal downwelling can contribute to intensification of larger or slower‐moving TCs before landfall. This result suggests that it is important to validate the modeling of coastal downwelling in future forecast models, in order to reliably forecast TC intensity near landfall. Key Points: Hurricanes approaching land tend to force downwelling over ocean shelves, especially when they move toward or with the coast to their right Coastal downwelling sustains warmer shelf sea‐surface temperatures (SSTs), even when storm‐induced ocean mixing might otherwise cool SSTs Sustained shelf SSTs increase heat and moisture fluxes contributing to larger or slower‐moving hurricanes' intensification near landfall